Experimental Investigation on the Drift and Collision of Containers Induced by Tsunami Action on a Wave Absorbing Revetment - Lee, Woo-Dong; Kim, Taeyoon; Kim, Jiwon; Kim, Seon-Ki; Oh, Hyeseong; Hwang, Taegeon (Han-guk haeyang gonghak hoeji (Online), 2024)
This study examined the collision dynamics between tsunami-driven drifting containers and port cranes, prompted by risks from the recent 7.6 magnitude earthquake and tsunami off Noto Peninsula, Japan. Hydraulic experiments were conducted to analyze container drift and collision forces using motion analysis software (DIPP-Motion) and a load cell installed on a crane leg model. The key parameters included the tsunami wave height, container weight (empty and loaded), initial position, and revetment type. The results suggested that higher tsunami wave heights led to more extraordinary inundation, allowing containers to float more efficiently, reducing bottom friction, and increasing drift speed and collision forces. The collision speeds ranged from 1.59 to 2.48 m/s, with collision forces of 45.18 to 77.68 N, representing increases of 6.45 to 15.58 times than no object. Heavier containers required deeper water to float, resulting in lower drift and collision speeds (0.88–0.89 times that of lighter containers). The wave-absorbing revetment caused higher flow velocities, producing collision speeds and forces 1.32–1.48 times greater than the vertical revetment. These findings highlight the importance of considering the tsunami magnitude, container weight, initial position, and revetment type in design, with face-to-face contact conditions crucial for estimating the maximum collision forces and preventing future tsunami damage.